Efficiency of Production Factors use of Corn Farming in Type C Tidal Land, Banyuasin Regency - Yudhi Zuriah Wirya Purba; Agoes Thony Ak; Faizal Daud (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2020)
Purba YZW, Thony Ak A, Daud F. 2020. Efficiency of production factors use of corn farming in type C tidal land, Banyuasin Regency. Journal of Suboptimal Lands 9(1): 89-101.The purpose of this study were to analyze the production factors affecting corn farming, the efficiency and elasticity of the use of production factors in corn farming. This research was conducted in Mulia Sari Village, Tanjung Lago District, Banyuasin Regency. A random sample of 30 corn farmers from 320 populations was employed in this research. The results showed factors that had a significant positive effect on corn production were the urea fertilizer and SP-36 fertilizer, while the factor of herbicides had a negative effect, and factors of labor, KCl fertilizer, insecticide and ZPT had no significant effect, labor and growth regulator were technically inefficient, while the urea, SP-36, KCl fertilizers, and insecticides were technically efficient. Overall, the use of production factors in corn farming was technically efficient in term of economy and price with the elasticity value by 0.925.